2023
DOI: 10.1039/d2cb00201a
|View full text |Cite
|
Sign up to set email alerts
|

Emerging approaches to CDK inhibitor development, a structural perspective

Abstract: This review summarises recent developments in structural characterisation of CDKs and alternative non-ATP competitive ways to inhibit them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 194 publications
0
7
0
Order By: Relevance
“…The ATP binding site and “Palm site” ( Figure 1A ) formed within the CDK2 N-terminal twisted β-sheet were identified by the monomeric CDK2 FragLite map. 29,47 However, the environment within the CDK2-cyclin A crystals leads to richer engagement at these sites. The CDK2-cyclin A map also highlights the CDK2 C-terminal lobe around the GDSEID sequence that precedes helix αG (13 events) ( Figure 1A ), the cyclin A RXL recruitment site (43 events) ( Figure 1A ), and a site formed at the interface between CDK2 and cyclin A (19 events) ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ATP binding site and “Palm site” ( Figure 1A ) formed within the CDK2 N-terminal twisted β-sheet were identified by the monomeric CDK2 FragLite map. 29,47 However, the environment within the CDK2-cyclin A crystals leads to richer engagement at these sites. The CDK2-cyclin A map also highlights the CDK2 C-terminal lobe around the GDSEID sequence that precedes helix αG (13 events) ( Figure 1A ), the cyclin A RXL recruitment site (43 events) ( Figure 1A ), and a site formed at the interface between CDK2 and cyclin A (19 events) ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Perturbing interactions made by CDK-cyclin complexes, particularly at SLiM sites, presents an opportunity to design more selective and discriminative probes of CDK function, which would bypass the orthosteric ATP binding site and provide specificity to both CDK activation states and particular signalling pathways. 29 Taking cyclin A as an example, truncation of RXL-containing substrates into peptidomimetic fragments has been explored both to optimise the cyclin binding motif to inhibit CDK-substrate interactions 9,22,3943 and to provide selective cyclin A binding moieties to enable early PROTAC design. 44 The ability of small molecule CDK inhibitors to perturb PPIs has recently been highlighted by the characterisation of inhibitors I-125A and I-198 that bind at the CDK2-cyclin E1 interface to remodel both a loop present in cyclin E1 and the activation segment of CDK2 to stabilise a structure that is not capable of peptide substrate recognition and catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are activated by cyclin binding to form cyclin-CDK heterodimers. The cyclin-CDK heterodimer regulates cell cycle progression ( Yousuf et al, 2022 ; Zabihi et al, 2022 ; Hope et al, 2023 ) and phosphorylates the upstream signals, including the retinoblastoma (Rb) protein ( Macaluso et al, 2006 ; Choi and Anders, 2014 ; Spring et al, 2020 ). The phosphorylated Rb induces the release of the critical transcription factor early 2 factor (E2F) to initiate the transcription of target genes, thereby facilitating the activation of various signaling pathways, including the G1/S transition, mitochondrial dynamics, and metabolism ( Sanchez-Martinez et al, 2015 ; Ingham and Schwartz, 2017 ; Matson and Cook, 2017 ; Sanchez-Martinez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shed light on the molecular mechanisms underlying the regulatory roles of CDKs in cell cycle progression and their inhibition by small molecules. (Arter et al 2022;Fassl et al 2022;Guiley et al 2019;Herrera-Abreu et al 2016;Hope et al 2023;Tadesse et al 2019;Whittaker et al 2017;Zhang et al 2021a) The CDK interacting protein/Kinase inhibitory protein (CIP/KIP) inhibitors bind to CDK2 complexes, hampering the kinase activity, while INhibitors of CDK4 (INK4) bind to CDK4 or CDK6, preventing their interaction with cyclin-D. (Fassl et al 2022;Guiley et al 2019;McGrath et al 2017) CDK4 and CDK6 inhibitors have shown efficacy in treating estrogen receptor-positive breast cancer and are now approved for clinical use. (Herrera-Abreu et al 2016) In the canonical cell cycle activation pathway, CDK4 is activated in the G1 phase, while CDK2 is involved in the G1/S transition and throughout the S-phase.…”
Section: Introductionmentioning
confidence: 99%